2016
DOI: 10.1016/j.soilbio.2015.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Lasting effect of soil warming on organic matter decomposition depends on tillage practices

Abstract: a b s t r a c tGlobal warming accelerates soil organic matter (SOM) decomposition with strong feedback to atmospheric CO 2 . Such an effect should be especially important for no-till agricultural practices, where SOM accumulates in the topsoil as compared with conventional tillage. We incubated soil samples (0e5 cm) at three temperature levels (15, 21 and 27 C) from long-term till and no-till systems that were in situ warmed and non-warmed to assess the temperature sensitivity of CO 2 efflux, labile organic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Increased temperatures promote soil warming, and warming significantly decreases SOC contents (Fang, Smith, Moncrieff, & Smith, ; Qi et al, ). Increased levels of soil respiration and mineralized C associated with increasing temperature may be responsible for SOC consumption (Allison, Wallenstein, & Bradford, ; Hou, Ouyang, Maxim, Wilson, & Kuzyakov, ; Lefèvre et al, ; Wu, Dijkstra, Koch, Peñuelas, & Hungate, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased temperatures promote soil warming, and warming significantly decreases SOC contents (Fang, Smith, Moncrieff, & Smith, ; Qi et al, ). Increased levels of soil respiration and mineralized C associated with increasing temperature may be responsible for SOC consumption (Allison, Wallenstein, & Bradford, ; Hou, Ouyang, Maxim, Wilson, & Kuzyakov, ; Lefèvre et al, ; Wu, Dijkstra, Koch, Peñuelas, & Hungate, ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that increasing temperature significantly hastens the cumulative CO 2 emission from the decomposition of peat soil MBC and DOC by an incubation experiment [44]. Rinnan et al [45] and Hou et al [46] also found that soil warming negatively affects the soil MBC. One possible explanation for this result is that the cell reserves and labile substrates for microbes are depleted under warming [46].…”
Section: Response Of Soil C and N Contents To Experimental Warmingmentioning
confidence: 88%
“…Rinnan et al [45] and Hou et al [46] also found that soil warming negatively affects the soil MBC. One possible explanation for this result is that the cell reserves and labile substrates for microbes are depleted under warming [46]. The results of our study indicated that warming exerted no evident effect on soil TC, which is consistent with the results of Chen et al [47].…”
Section: Response Of Soil C and N Contents To Experimental Warmingmentioning
confidence: 97%
“…Q 10 is the proportional change in soil respiration for a 10°C increase in temperature and may be used as an important approach to enhance our understanding of SOC dynamics. It allows the evaluation of different aspects, such as the role of the SOM lability, the temperature impact on the sequence in which organic material compounds are decomposed (Conant et al., ), the activity of soil microorganisms (Hou et al., ) and of soil texture (Wei et al., ). Our findings for the Q 10 index are consistent with studies that have addressed similar topics (Conant et al., ; Plante et al., ; Xu et al., ), where the most studied situations gave larger values of Q 10 for more resistant soil carbon.…”
Section: Discussionmentioning
confidence: 99%
“…More studies on SOC dynamics in semi‐arid conditions are needed, as temperatures above 30°C (INMET, ) are relatively common and can easily reach 40°C at the soil surface (Hamdi et al., ). Therefore, among the several variables that regulate the SOC decomposition, temperature has certainly gained attention (Conant et al., ; Cui et al., ; Hou, Ouyang, Maxim, Wilson, & Kuzyakov, ; Plante et al., ), and this theme has been approached in several aspects, such as the role of substrate availability (Hamdi et al., ); different soil types and tillage systems (Birge et al., ; Hou et al., ; Zhang, Li, Yang, & Sun, ), moisture levels (Richardson et al., ), and the responses of different SOM fractions (Carrillo, Pendall, Morgan, & Newcomb, ; Fang, Smith, Moncrieff, & Smith, ; Hou et al., ; Plante et al., ; Xu, Zhou, Ruan, Luo, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%